2017
DOI: 10.4018/ijwltt.2017100106
|View full text |Cite
|
Sign up to set email alerts
|

The Appropriateness of Scratch and App Inventor as Educational Environments for Teaching Introductory Programming in Primary and Secondary Education

Abstract: Teaching programming is a complex task. The task is even more challenging for introductory modules. There is an ongoing debate in the teaching community over the best approach to teaching introductory programming. Visual block-based programming environments allow school students to create their own programs in ways that are more accessible than in textual programming environments. These environments designed for education allow students to program without the obstacle of syntax errors (errors in typing command… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 55 publications
0
27
0
3
Order By: Relevance
“…In teaching programming to young students, teaching supported by a programming tool is regarded as important for children to make sense of programming more easily and particularly to love it (Chiang & Qin, 2018;Papadakis & Orfanakiz, 2016;Panselinas, et al, 2018;Papadakis, et al, 2017;Kalelioglu & Gulbahar, 2014;Shin, & Park, 2014;Uzgur & Aykac, 2016;Yildirim, 2017). Yildirim (2017) concluded that teaching with Scratch contributes to programming education in his study, which aims to develop a mobile application in Scratch programming language in order to improve the programming skills of middle school students.…”
Section: Introductionmentioning
confidence: 99%
“…In teaching programming to young students, teaching supported by a programming tool is regarded as important for children to make sense of programming more easily and particularly to love it (Chiang & Qin, 2018;Papadakis & Orfanakiz, 2016;Panselinas, et al, 2018;Papadakis, et al, 2017;Kalelioglu & Gulbahar, 2014;Shin, & Park, 2014;Uzgur & Aykac, 2016;Yildirim, 2017). Yildirim (2017) concluded that teaching with Scratch contributes to programming education in his study, which aims to develop a mobile application in Scratch programming language in order to improve the programming skills of middle school students.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, we can find several proposals for programming and CT teaching in a way that engages students with educational software or visual block-based programming environments [5,6]. For example, in [7], an analysis on the use of visual block-based programming for teaching introductory programming is presented using Scratch and App Inventor environments, and in [8], the combination of Lego Mindstorms and App Inventor is used for teaching novice programmers. In this line, in [9], a comparison between programming environments is carried out with the focus on secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…But in the last ten years, Chinese educators have sent a lot of talents to various fields, and the national economy has been greatly improved, so we have summarized China's educational methods [1] , this paper focuses on attaching importance on the primary and secondary education [2][3] . So what the foundation of national education is, how it has been conducted in the past ten years and how it has developed since [4][5] , by looking for different materials, carefully studying data from some online libraries and official websites [6][7][8] , this article focuses on the relationship between different variable sets [9] , take advantage of regression analysis tools to analyze today's China Primary and secondary education the trend of growth [10] .…”
Section: Introductionmentioning
confidence: 99%